THE STRATIGRAPHY AND GEOLOGICAL STRUCTURE IN KOTAAGUNG TIMUR DISTRICT, TANGGAMUS, LAMPUNG - Natalia, Happy Christin; Wiguna, Lanang Rangga Setia (Engineering Faculty Universitas Lampung, 2025)
Kotaagung Timur region, Tanggamus Regency, Lampung, is the focus area of this research. In general, the area has a unique and complex geological setting such as the variety of volcanic rocks, granite, and the Sumatran Fault System that through this area. Geological research aims to obtain geology dynamics about stratigraphy and geology structure in the research area. Two analyses have been done to achieve these goals, i.e., field observation, petrography analysis, and structural geology analysis. The stratigraphy units of the study area are composed of volcanic rocks, plutonic rocks, and surface deposits and can be divided into eleven lithostratigraphic units. The stratigraphy of the research area can be grouped into 5 groups, i.e., the Mount Gisting volcanic group, the granitoid pluton group, the Cawang Haro Mountains volcanic group, the Mount Tanggamus volcanic group, and the alluvial deposit. Geological structures are well developed, and the research area is cut by ten faults, such as dextral strike-slip faults, sinistral strike-slip faults, and reverse faults. Based on these things, the geological history of the study area started in the Late Oligocene with three episodes of volcanism. The first episode was Mount Gisting’s volcanism during the Late Oligocene-Early Miocene, followed by the granitoid intrusion. The volcanic products of the Cawang Haro Mountains in the Middle Miocene mark the second episode. The last volcanic episode occurred in the Holocene, it came from Mount Tanggamus’s volcanism. The development of the structural geology happened before the previous volcanism episode.